A compassionate pause. Issue 2 (February 2021) - Links, Matthew; Ayling, Terry; Doran, Joanne; Braganza, Shahina; Martin, Peter; Clayton, Josephine; Hiremagalur, Balaji
Highlights: Skilled communication depends on compassion in difficult situations. A brief pause before a difficult conversation allows time to focus mindfully on compassion. This is a practical and teachable intervention for multiple conversations.